Learning and Change Networks. (Kairaranga, 2015)
The Learning and Change Network Strategy (LCN) was developed to raise students’ achievement by appreciating, extending and enriching their learning environments. Throughout New Zealand there are 53 voluntary, networked communities of practice. They involve the active participation of students, teachers, parents, school leaders and community members from early childhood centres and primary, intermediate, secondary, and special education schools. Together the participants explore learning environments in relation to mutually-understood achievement challenges and make changes based on unique, contextually-specific analyses. Networks are observing impacts of this change on student outcomes and the practice of all participants. They have noticed that many children have made academic gains, collaboration within and between schools and communities has increased, and teachers, parents and students themselves have gained new insights into the students’ learning. Schools have benefited from the broadening of leadership and evaluative capability of staff and the transfer of in-depth methods of inquiry into school initiatives.